Manajemen Pembelajaran Program Diniyah Di SDIT Nurul Ishlah Banda Aceh - Ita Novita (Universitas Islam Negeri Ar-Raniry Banda Aceh, Aceh, Indonesia., 2019)
The effective and efficient of Diniyyah Learning Management Program is one of the supporting factors to achieve the learning objectives of diniyah program to produce a generation that is able to read al-Quran and has a true Aqidah and morality. The purpose of this research is to know the planning, implementation and evaluation of learning diniyyah program at SDIT Nurul Ishlah Banda Aceh. This research uses descriptive method with qualitative approach. Data collection technique is done through interview, observation and documentation. The subjects of this research are principal, head of diniyah program and teachers of diniyah at SDIT Nurul Ishlah Banda Aceh. The results showed that: 1) the learning plan of diniyah program prepared by diniyyah teachers is still many deficiencies, the teachers only prepare the material and the learning method. The Learning Implementation Plan is not written. 2) the Implementation of diniyah learning program implemented in SDIT Nurul Ishlah Banda Aceh has been done systematically and used various learning methods, so as to create a conducive and fun learning atmosphere; but in the use of learning media, many teachers only use the media in the classroom as learning, without presenting a variety of learning media. 3) the evaluation of diniyah teachers in SDIT Nurul Ishlah has been done systematically by evaluating the process and evaluating the learning outcomes at the end of each semester. The evaluation is done in the form of written test and practice test, and attitude evaluation through observation, and finally the evaluation results are given to each student in the form of a learning result report.